2020
DOI: 10.20944/preprints202003.0311.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pathological Study of the 2019 Novel Coronavirus Disease (COVID-19) through Post-Mortem Core Biopsies

Abstract: Data on pathologic changes of the 2019 novel coronavirus disease (COVID-19) are scarce. To gain knowledge about the pathology that may contribute to disease progression and fatality, we performed post-mortem needle core biopsies of lung, liver, and heart in four patients who died of COVID-19 pneumonia. The patients’ ages ranged from 59 to 81, including 3 males and 1 female. Each patient had at least one underlying disease, including immunocompromised status (chronic lymphocytic leukemia and renal tra… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
69
1
5

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(83 citation statements)
references
References 16 publications
6
69
1
5
Order By: Relevance
“…9,32 Previous reports of autopsy series of COVID-19 patients have also shown that exudative DAD is a major finding. [10][11][12][13] A mixed pattern of exudative/proliferative DAD, observed in most of our patients and also by others, indicates the progression of the lung injury, probably related to both the temporal evolution of the injury and the effects of mechanical ventilation. 7,10 Three of our patients showed a mixed pattern of DAD, even with a short period from symptom onset to death.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…9,32 Previous reports of autopsy series of COVID-19 patients have also shown that exudative DAD is a major finding. [10][11][12][13] A mixed pattern of exudative/proliferative DAD, observed in most of our patients and also by others, indicates the progression of the lung injury, probably related to both the temporal evolution of the injury and the effects of mechanical ventilation. 7,10 Three of our patients showed a mixed pattern of DAD, even with a short period from symptom onset to death.…”
Section: Discussionsupporting
confidence: 81%
“…[10][11][12][13] A mixed pattern of exudative/proliferative DAD, observed in most of our patients and also by others, indicates the progression of the lung injury, probably related to both the temporal evolution of the injury and the effects of mechanical ventilation. 7,10 Three of our patients showed a mixed pattern of DAD, even with a short period from symptom onset to death. Although there is a direct relationship between the duration of DAD and fibroproliferation, fibroproliferative changes may start early in the course of the disease.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…11 Another recent report, an analysis of core biopsies obtained postmortem from four COVID-19 patients with a minimum of 15 days of symptoms, describes DAD in all biopsies, with superimposed bacterial pneumonia in one. 12 The aim of this report is to share our observations on the pathology of COVID-19 based on complete autopsies in two individuals who died in Oklahoma during the COVID-19 pandemic and were found to be positive for SARS-CoV-2 by postmortem testing. We also wish to share our experience regarding the precautions and personal protective equipment (PPE) used during these autopsies.…”
mentioning
confidence: 99%